Christianity and the Development of Modern Healthcare in Taiwan - LI Xiuzhen, (Journal of Research for Christianity in China (JRCC), 2025)
Taiwan was the earliest region in China to receive Christianity (Protestantism), introduced by the Dutch in 1624. Dutch missionaries pioneered missionary strategies and educational approaches in China, though they did not engage in healthcare. With the end of Dutch colonial rule 38 years later, the Christian faith brought by missionaries quickly faded from Taiwanese society, leaving no lasting impact. When Western missionaries returned to Taiwan two centuries later, they adopted a different approach from their Dutch predecessors. They used the “scalpel” to pave the way for the “cross,” believing that to save souls, one must first save bodies. “This enabled modern missionaries to gain the initiative in evangelism almost effortlessly upon arriving in Taiwan.”